IMPACT OF FRICTION COEFFICIENT VARIATION ON TEMPERATURE FIELD IN ROTARY FRICTION WELDING OF METALS – FEM STUDY - ŁUKASZEWICZ, Andrzej; JÓZWIK, Jerzy; CYBUL, Kamil (Applied Computer Science, 2023)
A mathematical model is presented for investigating the temperature field caused by the rotary friction welding of dissimilar metals. For this purpose, an axisymmetric, nonlinear, boundary value problem of heat conduction is formulated with allowance for the frictional heating of two cylindrical specimens of finite length made of Al 6061 aluminium alloy and 304 stainless steel. The thermo-physical properties of materials change with increasing temperature. It was assumed that the coefficient of friction does not depend on the temperature. The mechanism of heat generation due to friction on the contact surface with the temperature field of samples is considered. The boundary problem of heat conduction was reduced to the set of nonlinear ordinary differential equations at time t relative to the values of temperature T at the finite elements nodes. The numerical solution of the problem was obtained with the inverse 2nd order differentiation method implemented in COMSOL FEM system (finite element method), with time step ∆t=0.1 (s). The influence of various values of friction coefficient is presented.